2012
DOI: 10.4161/psb.21900
|View full text |Cite
|
Sign up to set email alerts
|

Is polyphenol induction simply a result of altered carbon and nitrogen accumulation?

Abstract: C arbon translocation in plants isshaped by phyllotaxis and regulated by source/sink interactions that respond to the demands of growth and defense. We have studied this extensively in poplar saplings, and recently showed that unlike carbon import, nitrogen is not translocated to sink leaves in response to application of jasmonic acid. Here we report that this is also true for young trees in the field. We discuss the importance of transport processes in establishing local C:N ratios, and suggest that the JA-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…15 N transport from roots also was not disrupted by steam girdling, indicating that the 15 N label was largely restricted to xylem and independent of source-to-sink phloem flow (Appel et al, 2012a). This was confirmed in larger, 4-year-old trees, using whole branches, longer transport distances, and multiple sampling intervals (Arnold et al, 2004; Appel et al, 2012b). JA treatment led to significantly lower rates of 15 N import at 24, 48, and 72 h. It is possible that nitrogen from sources other than roots might have reached the elicited leaves (e.g., stems; Welter, 1989; Fan et al, 2009); that nitrogen would not be labeled and hence would not be detected.…”
Section: Types Of Resource Reallocations In Plant Defense Responsesmentioning
confidence: 56%
See 1 more Smart Citation
“…15 N transport from roots also was not disrupted by steam girdling, indicating that the 15 N label was largely restricted to xylem and independent of source-to-sink phloem flow (Appel et al, 2012a). This was confirmed in larger, 4-year-old trees, using whole branches, longer transport distances, and multiple sampling intervals (Arnold et al, 2004; Appel et al, 2012b). JA treatment led to significantly lower rates of 15 N import at 24, 48, and 72 h. It is possible that nitrogen from sources other than roots might have reached the elicited leaves (e.g., stems; Welter, 1989; Fan et al, 2009); that nitrogen would not be labeled and hence would not be detected.…”
Section: Types Of Resource Reallocations In Plant Defense Responsesmentioning
confidence: 56%
“…The strong connection between regulation of source/sink relations and pathogen success makes sink-regulating apoplastic invertases a key part of plant defense against microbes, too (Berger et al, 2007). It seems clear that long-distance transport of resources is a component of plant defense responses to insects and pathogens (Truernit and Sauer, 1995; Arnold and Schultz, 2002; Roitsch et al, 2003; Roitsch and González, 2004; Matyssek et al, 2005; Appel et al, 2012a, b). …”
Section: Types Of Resource Reallocations In Plant Defense Responsesmentioning
confidence: 99%
“…Defense hormones (such as JA) may also enhance C translocation to natural plant sinks by increasing invertase activity as a means to increase defense compound synthesis and potentially compensate for herbivore-induced reductions in photosynthesis (26,27). We observed nearly universal up-regulation of transcripts encoding JA synthesis and up-regulation in vacuolar invertase transcripts (Fig.…”
mentioning
confidence: 79%
“…Here, we showed that induction responses differ spatially with respect to the location of the damage and depend on constitutive levels. Many factors can influence the concentrations and inducibility of phytochemicals, including plant tissue age (Koricheva and Shevtsova 2002), vascular architecture and physiology (Arnold and Schultz 2002;Arnold et al 2012;Jones et al 1993), and priming via volatile organic compounds emitted from neighboring damaged tissues (Frost et al 2007). More research is needed to examine the collective influence of these factors on the spatial patterns of carbon-and protein-based plant defense traits at the canopy scale.…”
Section: Discussionmentioning
confidence: 99%